The challenge of creating a 'Welsh NHS'. (January 2016) - Riley, Christopher
Health policy in the UK has been greatly affected by devolution, with growing divergence in policy and practice across the four UK countries. Since 1999, Wales has created distinctive policies and structures and made some progress in improving health and services, despite obstacles. These include financial and demographic challenges faced elsewhere and others rooted in local attitudes and expectations and in the nature of the Welsh constitutional settlement.